Syrian intervention in Lebanon : the 1975-76 civil war - Weinberger, Naomi Joy (OUP E-Books., 1986)
Conflict and intervention in the Middle East are not uncommon occurrences. Yet when civil strife erupted in Lebanon in 1975, the events that followed were unusual indeed. Unlike most patterns of intervention, Syria displayed remarkable tactical flexibility by first intervening on behalf of the rebels, its traditional allies, then shifting its allegiance mid-war to the Lebanese incumbents. Also, whereas most intervention scenarios end with a process of decommitment, Syria eventually occupied parts of Lebanon to become an enduring military entity there. Delving into primary Syrian and Lebanese s.